2022
DOI: 10.4103/iju.iju_222_21
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of freehand transperineal prostate biopsy under local anesthesia

Abstract: Introduction: With the emergence of multidrug-resistant organisms causing urosepsis after transrectal biopsy of prostate, the need for an alternative approach has increased. We assessed the safety and feasibility of transrectal ultrasound (TRUS) guided free-hand transperineal prostate biopsy under local anesthesia (LA) for suspected prostate cancer. Materials and Methods: This prospective study was conducted from July 2019 to December 2020 in which pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…But transperineal biopsies are preferred now, with the advantage of less infections and higher yield from anterior gland biopsies and apical biopsies. 19 Targeted biopsies from hypoechoic and other suspicious areas can be done in addition to standard cores.…”
Section: Transrectal Ultrasound Guided Biopsymentioning
confidence: 99%
“…But transperineal biopsies are preferred now, with the advantage of less infections and higher yield from anterior gland biopsies and apical biopsies. 19 Targeted biopsies from hypoechoic and other suspicious areas can be done in addition to standard cores.…”
Section: Transrectal Ultrasound Guided Biopsymentioning
confidence: 99%
“…[ 4 5 ] Multiple studies compared TP biopsy to other techniques showed that it is safe, feasible, has superior sensitivity, especially in detecting anterior cancers as well as having low rate of sepsis. [ 6 7 ] Introduction of freehand techniques avoided discomfort and complicated setting up brachytherapy stepper and proved to be safe, accurate, and feasible. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%